Numerical Calculation of Electric Fields in Housing Spaces due to Electromagnetic Radiation from Antennas for Mobile Communication - H.-P. Geromiller (Acta Polytechnica, 2004)
The influence of electromagnetic radiation from mobile antennas on humans is under discussion in various group of scientists. This paper deals with the impact of electromagnetic radiation in housing spaces. The space is assumed to be bordered by 5 walls of ferroconcrete and a door-window combination on the 6th side, the latter to be electromagnetic transparent. The transparent side of the housing is exposed to an electromagnetic wave. As the source of radiation is considered to be far away from the housing, the radiation is regarded as a plane wave. Due to the high signal frequency and the ferroconcrete walls, 5 sides of the housing space are considered to be perfect conductors. The electric field inside the housing is calculated numerically by the method of finite differences for different angles of incidence of the radiated electromagnetic wave. The maximum value of the calculated electric field is outlined in a diagram.